Mechanical Thrombectomy for Acute Ischemic Stroke. Issue 2 (April 2023) - Sheth, Sunil A.
ABSTRACT: OBJECTIVE: Endovascular stroke therapy has greatly improved the ability to treat the deadliest and most disabling form of acute ischemic stroke. This article summarizes some of the recent innovations in this field and discusses likely future developments. LATEST DEVELOPMENTS: At present, there is robust activity to improve all facets of care for patients with large vessel occlusion stroke, including better prehospital routing, more efficient in-hospital screening, expanding indications for thrombectomy eligibility, innovating novel thrombectomy devices, and improving the effects of recanalization on clinical outcomes. In addition, the integration of endovascular stroke therapy (EVT)—an emergent and frequently off-hours procedure that requires a specialized team of nurses, technologists, and physicians—into acute stroke care has transformed referral patterns, hospital accreditation pathways, and physician practices. The eligibility for the procedure will potentially continue to grow to include patients screened without advanced imaging, larger core infarcts, and more distal occlusions. ESSENTIAL POINTS: In this review, we discuss the current state of EVT and its implications for practice, and present three cases that highlight some of the directions in which the field is moving.